Zwei kleine Bemerkungen zum semitischen Einfluss in Ägypten - Bojowald, Stefan (Biblische Notizen, 2010)
This article deals with two problems of the Egyptian-Semitic language exchange. In the first case, a new interpretation for the determinative “Reverse-running legs” after “Ir” “El” is looked for. The second part tackles the word “xDa” in o BM EA 50727, verso 7, written syllabically, whose old explanation as representing the Hebrew word “חזה ” “see” is rejected in favour of the Arabic word “° jf” “deceive”.